Duolingo Application as A Learning Aid to Enhance Vocabulary Proficiency in Procedure Texts at Junior High School - Mei Tri Wahyu Saputri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to investigate the effectiveness of Duolingo in improving vocabulary mastery related to procedure texts among 26 seventh-grade students at MTSS Daarul Ulum Margomulyo Blitar. The researchers employed a pre-experimental design using a one-group pre-test and post-test approach. The research process included three key steps: 1) administering a pre-test, 2) providing treatment, and 3) conducting a post-test. Data was collected through testing and analyzed using SPSS25. The results indicated that students' vocabulary achievement increased from an average of 61.15 in the pre-test to 83.65 in the post-test. The analysis revealed a significance value (sig2-tailed) of 0.001, which is below 0.05, indicating that Duolingo effectively enhanced the vocabulary achievement of the seventh-grade students at MTSS Daarul Ulum Margomulyo Blitar. Based on these findings, it is recommended that English teachers consider using Duolingo as an alternative instructional tool, particularly for teaching vocabulary and potentially other language skills or subskills.